Charms of evident identity - Čepulis, Nerijus (Religija ir kultūra, 2009)
In this article I seek to rethink the traditional notion of identity. In the tradition of Western thought identity was viewed first and foremost from an ontological point of view. After the turn toward the subject, the I is thought of as the centre, the base and the producer of any identity. Phenomenological analysis deepens the origin of identity to the relation of the I to the world, i.e. to the alterity. Yet the alterity, by becoming the content of consciousness, is not an absolute alterity. The way, in which identity assimilates, possesses the world and annihilates alterity, is representation. Representation seeks evidence. Representation as intentional perceptivity localizes every object in the light of consciousness. Light and vision are paradigmatic metaphors of the traditional Western thought. Hence in this article I seek to show why and how light and evidence do not tolerate absolute alterity. Identity can be sobered from the charms of evidence only by responsible relation to the Other, i.e. by ethics. Here identical subject loses the right of priority in front of the imperative of the other person. Idea of infinity worries total identity from within. Infinity does not permit identity to quiet down and induces to heed transcendence and alterity. Only in this way alterity can escape the violence to become a content of egocentrical identity and the victim of manipulation. Responsibility in the face of the other person precedes evident perception and legitimates the latter.
Keywords: identity; evidence; alterity; sociality